Experimental investigation and simulation of commercial absorption chiller using natural refrigerant R717 and powered by Fresnel solar collector - I. Boukholda; N. Ben Ezzine; A. Bellagi (International Journal of Thermofluids)
In this article, we present preliminary results from testing a solar refrigeration system. These tests were conducted on a Robur commercial refrigeration unit with a cooling capacity of 12 kW. The chiller operates on a modified single-effect absorption cycle and uses an aqueous ammonia solution as working fluid mixture. The system is powered by a field of Fresnel solar collectors.The experimental device equipped with the necessary metrological sensors is connected to a computer to monitor and store measurement data during the 24 h of testing. Experimental results show that the temperature of the heat transfer fluid can reach 190 °C and that of the chilled water leaving the evaporator -7.8 °C. The average coefficient of performance of the chiller is 0.65.To gain more insight in the internal operation of the chiller, first a steady-state simulation model of the machine was elaborated using the Aspen-Plus platform. The good agreement between the calculated and experimental performances indicates that the simulation model has correctly taken into account the main complex heat and mass transfer processes occurring in the different components of the chiller. In a second stage, a dynamic model of the chiller, more adapted to the refrigeration systems driven by intermittent solar energy, has been developed. The effect of heat source temperature on machine behavior was investigated. The results show that temperatures above 200 °C, such as those provided by linear Fresnel sensors for example, are not necessary, as the temperature and pressure evolutions inside the chiller are only slightly affected by these higher temperatures.